Reputational contagion and optimal regulatory forbearance - Alan D. Morrison; Lucy White (European Central Bank (ECB), 2010)
This paper examines common regulation as cause of interbank contagion. Studies based on the correlation of bank assets and the extent of interbank lending may underestimate the likelihood of contagion because they do not incorporate the fact that banks have a common regulator. In our model, the failure of one bank can undermine the public's confidence in the competence of the banking regulator, and hence in other banks chartered by the same regulator. Thus depositors may withdraw funds from their, unconnected, banks. The optimal regulatory response to this `panic' behaviour can be to privately exhibit forbearance to the initially failing bank in the hope that it - and hence other vulnerable banks - survives. By contrast, public bailouts are ineffective in preventing panics and must be bolstered by other measures such as increased deposit insurance coverage. Regulatory transparency improves confidence ex ante but impedes regulators' ability to stem panics ex post.
Keywords: G21; G28; 330; Bank Regulation; Contagion; Reputation; Bankenregulierung; Bankenaufsicht; Reputation; Bankenkrise; Ansteckungseffekt; Einlagengeschäft; Theorie